Selected country experiences during the pandemic: Policy responses and CGIAR support - Andam, Kwaw S.; Ezekannagha, Oluchi (International Food Policy Research Institute, 2022)
With the onset of the COVID-19 pandemic, CGIAR pivoted its research planning to better support countries as they responded to the crisis. Despite the unprecedented, highly disruptive nature of the pandemic, CGIAR’s collaborative country work has enhanced engagement across the agrifood sector, leveraged existing capacities, and improved awareness of vulnerabilities within value chains. The insights gained from this experience may ultimately prove useful in addressing other longstanding challenges as well. In this chapter, we recount selected country experiences during the pandemic and the response of the international agricultural research system to support these countries. In the section on country experiences, we draw from IFPRI’s COVID-19 Policy Response Portal (CPR) to focus on lockdown policies in Bangladesh, Kenya, and Nigeria. We describe the steps taken by governments in these countries to address challenges in the agrifood sector and provide social protection to the vulnerable.